2022
DOI: 10.3389/fmicb.2022.827371
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome as a Potential Biomarker in Fish: Dietary Exposure to Petroleum Hydrocarbons and Metals, Metabolic Functions and Cytokine Expression in Juvenile Lates calcarifer

Abstract: The gut microbiome of fish contains core taxa whose relative abundances are modulated in response to diet, environmental factors, and exposure to toxicogenic chemicals, influencing the health of the host fish. Recent advances in genomics and metabolomics have suggested the potential of microbiome analysis as a biomarker for exposure to toxicogenic compounds. In this 35-day laboratory study, 16S RNA sequencing and multivariate analysis were used to explore changes in the gut microbiome of juvenile Lates calcari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Based on our result, the abundant Lactobacillus in the skin could be considered the best biomarker candidate for tuna to monitor the host health status and environmental quality. It has been also proposed as a biomarker for toxicogenic exposure (Spilsbury et al, 2022).…”
Section: Microbial Biomarkers Provide Insights Into the Microecologic...mentioning
confidence: 99%
“…Based on our result, the abundant Lactobacillus in the skin could be considered the best biomarker candidate for tuna to monitor the host health status and environmental quality. It has been also proposed as a biomarker for toxicogenic exposure (Spilsbury et al, 2022).…”
Section: Microbial Biomarkers Provide Insights Into the Microecologic...mentioning
confidence: 99%
“…In this study, gut microbial diversity were negatively impacted by the PBM-based diet along with an enrichment of the Photobacterium genus. The prevalence of this genus was recently reported to increase in the gut system of barramundi when exposed to a variety of environmental stresses ( 48 ). In the present study, the observed bacterial dysbiosis in the intestine of barramundi fed PBM protein only was aligned with the results of the negatively altered mucosal barriers and expression of inflammatory cytokines and i-mucin c .…”
Section: Discussionmentioning
confidence: 99%
“…Rubritalea is a marine bacterium found in various environments, such as the Mediterranean sponge Axinella polypoides, juvenile Lates calcarifer, and shrimp infected with White Feces Disease [62, 113,117]. Certain strains of Rubritalea produce carotenoid compounds, resulting in the pink coloration of cell biomass.…”
Section: Gut Microbiota Of Juvenile Takifugu Rubripesmentioning
confidence: 99%